Shop drawing of hidden framing glass curtain wall aluminum alloy doors & windows SF06A-SF10B (RFA-013_Rev D) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.